Enhances A Villages Welfare By Updating Village Fund Allocations And Village Policies - Milanie, Feby (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2023)
The purpose of this research is to examine the influence of the benefits of village fund allocation, the benefits of village funds, and village policies on community welfare. This is also done to find out whether the benefits of village fund allocations, the benefits of village funds or village policies are equally influential on community welfare. All data is processed by multiple regression analysis by looking at the validity test, reliability, and hypothetical testing with the F test t test and determination test. The results of this study indicate that the benefits of village fund allocation, the benefits of village funds have an effect on community welfare while village policies have no effect on community welfare, and the benefits of village fund allocation, the benefits of village funds and village policies are equally influential on community well-being. and village policy both affect the welfare of community.